Use of 3D geometry modeling of osteochondrosis-like iatrogenic lesions as a template for press-and-fit scaffold seeded with mesenchymal stem cells - Krupa, P; Krsek, P; Javorník, M; Dostál, O; Srnec, R; Usvald, D; Proks, P; Kecová, H; Amler, E; Jancár, J; Gál, P; Plánka, L; et al. (Physiological research, 2007)
Computed tomography (CT) is an effective diagnostic modality for three-dimensional imaging of bone structures, including the geometry of their defects. The aim of the study was to create and optimize 3D geometrical and real plastic models of the distal femoral component of the knee with joint surface defects. Input data included CT images of stifle joints in twenty miniature pigs with iatrogenic osteochondrosis-like lesions in medial femoral condyle of the left knee. The animals were examined eight and sixteen weeks after surgery. Philips MX 8000 MX and View workstation were used for scanning parallel plane cross section slices and Cartesian discrete volume creation. On the average, 100 slices were performed in each stifle joint. Slice matrices size was 512 x 512 with slice thickness of 1 mm. Pixel (voxel) size in the slice plane was 0.5 mm (with average accuracy of +/-0.5 mm and typical volume size 512 x 512 x 100 voxels). Three-dimensional processing of CT data and 3D geometrical modelling, using interactive computer graphic system MediTools formerly developed here, consisted of tissue segmentation (raster based method combination and 5 % of manual correction), vectorization by the marching-cubes method, smoothing and decimation. Stifle- joint CT images of three individuals of different body size (small, medium and large) were selected to make the real plastic models of their distal femurs from plaster composite using rapid prototyping technology of Zcorporation. Accuracy of the modeling was +/- 0.5 mm. The real plastic models of distal femurs can be used as a template for developing custom made press and fit scaffold implants seeded with mesenchymal stem cells that might be subsequently implanted into iatrogenic joint surface defects for articular cartilage-repair enhancement.
Keywords: Femur; Prosthesis Design; kultivované buňky; design s pomocí počítače; Swine, Miniature; tkáňové podpůrné struktury; Tissue Engineering; Radiographic Image Interpretation, Computer-Assisted; Tomography, X-Ray Computed; osteochondritida; Disease Models, Animal; Stifle; Mesenchymal Stem Cells; Computer-Aided Design; miniaturní prasata; protézy - design; Tissue Scaffolds; Cells, Cultured; mezenchymální kmenové buňky; Swine; modely nemocí na zvířatech; rentgenový obraz - interpretace počítačová; zvířata; zobrazování trojrozměrné; tkáňové inženýrství; anatomické modely; Models, Anatomic; Imaging, Three-Dimensional; prasata; femur; počítačová rentgenová tomografie; kolenní kloub u koně, psa; Osteochondritis; Animals